Plant functional groups and soil properties vary with the restoration periods in Zoige desertification land - Wang, Ruolan; Lou, Yuanxin; He, Li; Chen, Juanli; Chen, Yali; Yan, Wuxian; Deng, Dongzhou; Mu, Junpeng (Frontiers in Ecology and Evolution, 2023)
Desertification has a significant impact on the Zoige meadow. Research efforts are directed towards the rehabilitation of the Zoige desertified alpine meadow, specifically in understanding the soil's physical and chemical characteristics and the functional groupings of plants. However, the relationships between plant functional groups and soil properties remains uncertain. The primary objective of this study is to investigate the correlation between plant functional groups and soil nutrients across various stages of restoration. This study examined important value of plant functional groups, as well as variations in several soil characteristics, such as soil total nitrogen, total carbon, total phosphorus, available nitrogen, available potassium, available phosphorus, and soil pH during the stages of recovery. The results showed that the relative significance of importance values differed across distinct functional groups during different stages of recovery. The important value of legumes was found to have a strong negative correlation with the levels of soil available nitrogen and potassium.In contrast, there was a substantial positive correlation between the important value of grass and both soil total carbon and available potassium. Conversely, there was a strong negative relationship between the importance value of sedges and both total soil carbon and phosphorus. These findings indicate that the linkages between soil properties and plant functional groups varied across different recovery periods. This study would shed new light on the restoration in the Zoige desertified alpine meadows.